(untitled) (Reflection and Critique Law Magazine, 2022)
This article deals with the founded probable cause for prosecution, normative element of the criminal description of art. 30 of the new Abuse of Authority Act (Law 13.869/2019), and aims to elucidate its meaning, in order to guide the interpretation and application of the provision and offer beacons and cautions regarding the persecutory activity, especially the Public Prosecution Service’s, mainly about the possibility of its deflagration based on anonymous delation. It analyses art. 30 of the AAA’s structure and its correlation with the dispositions of arts. 1 and 2 of the legal text. It examines the founded probable cause in the context of the degrees or levels of depth of the cognition proper to Procedural Law. It makes considerations about the founded probable cause in the face of anonymous delation and proposes cautions in the way of proceeding.